Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan - M. Effendi; Febrie Yogie (Journal of Management and Bussines (JOMB), 2019)
This research was conducted to determine the effect of motivation and work discipline on the performance of Division 03 employees of PT. PP London Sumatra Indonesia Tbk. Bukit Hijau Rawas Ilir District, North Musi Rawas Regency. In this study used a three item variable questionnaire method namely motivation questionnaire (X1), work discipline (X2) and employee performance variable (Y). The data analysis technique used is the Analysis of Multiple Linear Regression, Coefficient of Determination (R2), and Test F. The results of the study, from the results of multiple linear regression analysis the equation Y = 10.428 + 0.349 X1 + 0.382 X2. Furthermore, from the analysis obtained the R square R2 value of 0.770 or 77.0%. This value gives the understanding that motivation (X1), and work discipline (X2) contribute 77.0% to employee performance (Y). While the remaining 23.0% is influenced by other variables not included in this study. Conclusion, there is a simultaneous influence between motivation and work discipline on employee performance Keywords: Motivation, Work Discipline, Performance